Resistance Drift of Phase Change Materials Beyond the Power Law - Jakob Ballmaier; Sebastian Walfort; Martin Salinga (Advanced Electronic Materials)
Abstract Phase change materials (PCMs) are used in fast, non‐volatile memory applications, where the information is encoded in the electrical contrast between a conductive crystalline and a resistive amorphous state. In principle, the resistance of a single device can be programmed in a near continuous manner by tuning the amorphous to crystalline volume ratio. This makes PCMs interesting for novel analog computing architectures. Here, a key challenge remains in either mitigating or even utilizing a characteristic of the amorphous state: Its resistance evolves with time. Because this so‐called resistance drift is captured on typical experimental timescales by an otherwise featureless power law, it can be described by a variety of physical models, leaving the true underlying microscopic origin obscured. Using both electrical and ultrafast optical heating pulses, the resistance drift is resolved over 11 orders of magnitude in time down to the first nanoseconds after formation of the amorphous state. Clear deviations from the power law both on short timescales below 1 µs and, at elevated temperatures, also on longer timescales of seconds are observed. The observations are discussed in view of common drift models. Moreover a unifying energy landscape picture is offered as an interpretation of the experimental evidence.